Academic Libraries in The Digital Transformation: The Case of the Library of the Faculty of Economics of Porto - Ferreira, Mariana; Preto, Paulina; Braga, Inês (Bobcatsss, 2023)
different means, for the training of students. This work aims to show how a university library - that of the Faculty of Economics of the University of Porto (FEP) - meets the needs of students, namely in terms of information literacy (IL) and digital literacy (DL), using for this the new technologies which enable the referred digital transformation and new ways of teaching and learning. Due to the current importance of the librarian's role as a trainer, the authors - the trainee of the degree in Documentation and Information Sciences and Technologies (LCTDI) of the Higher Institute of Accounting and Administration of Porto (ISCAP), the FEP librarian and the internship advisor - designed a set of training sessions for IL within the scope of the curricular internship of said course in the academic year 2019-20. This project had as main objectives: (1) to provide distance learning; (2) to reduce the on-site training provided by the library; (3) to allow any member of the FEP community to have access to information that is relevant to them, whenever and wherever they want; (4) to offer training to the entire educational community, including Erasmus students, with the production of materials in Portuguese and English. The methodology adopted consisted of a review of the literature on the subject and a practical part carried out in the library involving the production of videos based on the observation of training sessions. From a theoretical point of view, the themes of IL and DL in AL are addressed, the role of the librarian in the development of such skills in students, the exploration of new digital tools used for training, more specifically, the production of tutorial videos, as well as distance learning. In the practical component of this project, eight video tutorials were produced on the search and location of information using the online catalog, the subject of one of the training activities given by the FEP library, and which addresses the most basic resources of the library, which is an essential resource for students. In conclusion, the creation of support materials that will soon be made available on the institution's website will surely contribute to the development of IL skills of a greater number of students. In addition, the new format of these contents will serve as a complement and / or substitute for face-to- face training sessions, responding to a problem detected by the institution itself - that the training for IL is not sufficient nor the most diversified among the academic community. Finally, the sharing and availability of information designed with a specific target audience in mind and disseminated through the right communication channels, is crucial for a profitable use, leading to the consequent satisfaction of users.